Quality of Life and Psychometric Characteristics of Syrian Refugee Physicians Who Migrated to Turkey: A Cross-Sectional Study - Ahmet Keskin; Basri Furkan Dagcioglu (International Journal of Clinical Practice)
Background. The concept of migration comes with various problems, affecting the quality of life and psychological state of immigrants. This study aimed to investigate the quality of life and depression and anxiety states of physicians who immigrated to Turkey after the civil war that started in Syria in 2011. Methods. In this cross-sectional study, a sociodemographic questionnaire form, the short version of the World Health Organization’s quality of life assessment tool (WHOQOL-BREF), Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI) were applied to Syrian doctors who received integration training to work in refugee health centers established for immigrants in Turkey. Results. A total of 570 participants were included in the study. The median scores of WHOQOL-BREF domains of the participants were 75 for DOM1 (min: 25, max: 100, IQR: 18), 69 for DOM2 (min: 6, max: 100, IQR: 25), 69 for DOM3 (min: 0, max: 100, IQR: 19), and 63 for DOM4 (min: 0, max: 94, IQR: 19). The median BDI score of the participants was 7 (min: 0, max: 41, IQR: 8), and the median BAI score was 5 (min: 0, max: 50, IQR: 8). Having primary care experience, having knowledge about the Turkish healthcare system, believing that they can adapt to work in refugee health centers, and not having a plan to return to their country were found to be associated with a higher score in at least one of the WHOQOL-BREF subdomains. Planning to turn back their country was significantly associated with higher BAI scores. Conclusions. The overall quality of life of most refugee physicians in Turkey was high, and the BDI and BAI scores were also below the threshold values. Further qualitative studies that allow in-depth analyses may reveal underlying factors for this situation.